Solve the system of equations using substitution. 3y = –x + 2 y = –x + 9 (–1, 8) (3, 6) (10, –1) (20, –4)

Respuesta :

Answer:

Step-by-step explanation:

The system of equations are

3y = - x + 2 - - - - - - - - - - - -1

y = - x + 9 - - - - - - - - - - - - -2

The first step is to substitute equation 2 into equation 1, it becomes

3(- x + 9) = - x + 2

-3x + 27 = - x + 2

Adding x to the left hand side and the right hand side of the equation and also subtracting 27 from the left hand side and the right hand side of the equation, it becomes

-3x + x + 27 - 27 = - x + x + 2 - 27

- 2x = - 25

Dividing the left hand side and the right hand side of the equation by - 2, it becomes

x = - 25/ -2 = 12.5

Substituting x = 12.5 into equation 2, it becomes

y = - 12.5 + 9 = - 3.5

x = 12.5

y = - 3.5